Effectiveness of Liquid Waste Treatment of RSUD Kefamenanu Through Filtration Process - Yanti Benyamin; Suwari Suwari; Dodi Darmakusuma (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2020)
Hospital liquid waste has the potential to pollute the environment and harm health if not processed properly because it contains high enough organic and inorganic compounds, pathogenic microorganisms, toxic chemicals and radioactive substances. Rumah Sakit Umum Daerah (RSUD) Kefamenanu is the only hospital owned by the Government of Kabupaten Timor Tengah Utara and located in the middle of community settlements and uses wastewater treatment plants (IPAL) in the treatment of hospital liquid waste since 2016. The results of liquid waste quality examination showed that there are several parameters that have increased after processing through IPAL so that researchers use filtration method in processing liquid waste of RSUD Kefamenanu. This study aims to find out the effectiveness of liquid waste treatment of RSUD Kefamenanu through filtration process using filter media in the form of coconut coir, sand, palm oil, activated charcoal and zeolite. This research is a pseudo experiment, namely to find out the percentage of decreased levels of liquid waste parameters through the filtration process. The results showed that the levels after processing had an average value of BOD 3.86 mg/L, TSS 14 mg/L and ammonia of 0.10 mg/L. The filtration process was able to lower BOD levels by 63.62%, TSS by 93.24% and ammonia by 86.57%. Based on these results, it can be concluded that the filtration process is able to lower levels of BOD, TSS and ammonia in liquid waste of RSUD Kefamenanu.